Geomechanical Characteristics of Natural and Stabilised Black Cotton Soils from the Accra Plains of Ghana - Gidigasu, Solomon Senyo Robert (2014)
A thesis submitted to the Department of Geological Engineering of the Kwame Nkrumah University of Science and Technology in fulfilment of the requirements for the award of the degree of Master of Philosophy in Geological Engineering.